DETERMINAN PENGELOLAAN DANA DESA - Insani, Amin; Fachriadi, Tengku; Sariwanti, Eva (Politeknik Negeri Ambon, 2025)
Introduction: This study aims to determine the effect of Accountability, Transparency and Apparatus Competence on Village Fund Management empirically.Methods: The method in this study is research with a quantitative approach, the population used is all Village Apparatus in villages in Kerinci kanan sub-district, Siak district with a sample used as many as 96 Apparatus. For data analysis using Structural Equation Modeling (SEM) using Smart PLS softwarte version 4.0.Results: The results of this study indicate that Transparency has a positive effect on Village Fund Management. Apparatus competence has a positive effect on Village Fund Management, while accountability has no effect on village fund management, which can be seen from the results of hypothesis testing using the bootstrapping method in Smart PLS Version 4.0.Keywords: Accountability, Transparency, Apparatus Competence, Village Fund Management